Systemic and local associated disorders in children with congenital cataracts-a retrospective analysis - Baig, Rashid; Rahman, Asma; Jehanzeb, Hamzah; Khadijah Abid, (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the systemic and local disorders associated with congenital cataracts in children in a tertiary care setting. Method: The retrospective study was conducted at the Department of Ophthalmology and Visual Sciences, Aga Khan University Hospital, Karachi, and comprised data from January 2014 to December 2019 of patients aged <12 months who underwent lens aspiration. Data on demographics, family history, maternal illness, and associated systemic and local disorders were collected through chart reviews. Unilateral and bilateral cataracts were stratified. Data was analysed using RStudio. Results: Of the 84 cases evaluated, 81(96.4%) were analysed after excluding incomplete records; 41(50.6%) boys and 40 (49.4%) girls. The median age at presentation was 6 months (interquartile range: 4-11 months). Bilateral cataracts were more common (n=50, 61.7%) than unilateral cataracts (n=31, 38.3%). Only 2 (2.5%) cases had a family history of congenital cataracts. Systemic associations included cardiac abnormalities (n=4, 4.9%), central nervous system anomalies (n=3, 3.7%), hearing impairment (n=1, 1.2%), and genitourinary malformations (n=1, 1.2%). Chromosomal anomalies (n=3, 3.7%) and inborn errors of metabolism (n=3, 3.7%) were also noted. Conclusion: The burden of congenital cataracts was significant and its aetiology was multifactorial, emphasising the need for early detection and a multidisciplinary approach to management. Key Words: Blindness, Children, Congenital cataracts, Local disorders, Systemic disorders.